The role of women in the informal sector economic in the peri urban area of Makassar - Rahman, Abdul (Research Agency for Humanity and Urban, 2025)
This study aims to determine the role of women in the informal sector in improving family welfare in Sumanna Village. This study employed qualitative research, analyzed and written descriptively. Data collection techniques used observation, interviews, and documentation. The results indicate that: In addition to their roles as wives and mothers, women also play a role in assisting their husbands in earning a living, such as selling fish at the market, selling cakes, selling mixed goods, and other informal activities. Women who play a role in improving family welfare in Sumanna Village are helping to increase family income which is not comparable to the amount of income earned by their husbands with the needs of the family and the choice to work to help their husbands in earning a living is a choice that must be made. Before deciding to work, they have also obtained permission from their husbands, they help each other, support each other's work and continue to carry out their obligations as wives and mothers at home.